Unsolicited Proposals : The Issues for Private Infrastructure Projects - World Bank (Washington, DC, 2012)
Many of the world's most controversial private infrastructure projects originated as unsolicited proposals to governments. This Note explores critical questions for developing policies to deal with unsolicited proposals. For example, under what conditions should governments allow unsolicited proposals? And how can they add competition and transparency to the process? A companion Note reviews the methods used by the governments of Chile, the Republic of Korea, the Philippines, and South Africa to transform unsolicited proposals into competitively tendered projects.